Better detection of Demodex mites by Löffler’s alkaline methylene blue staining in patients with blepharitis - Kiuchi K (Dove Medical Press, 2018)
Katsuji KiuchiKiuchi Eye Clinic, Joto-ku, Osaka, JapanPurpose: To determine whether the Löffler’s alkaline methylene blue staining method is better than no staining in detecting Demodex mites in the eyelashes of patients with blepharitis.Materials and methods: Eyelashes were collected from 22 patients with blepharitis. The mean age of the patients was 82.5±6.2 years (± SD) with a range from 71 to 93 years. Eyelashes were epilated by forceps and placed individually on microscope slides. The number of Demodex mites was determined by conventional optical microscopy before and immediately after the addition of the methylene blue staining solution.Results: The mean Demodex count before the addition of the methylene blue solution was 2.9±2.9, and it was 4.4±3.9 after the addition of the methylene blue solution (P<0.01, Wilcoxon test).Conclusion: The methylene blue staining method is a simple and useful method in detecting the presence and quantifying the number of Demodex mites. We recommend the methylene blue staining method not only for the diagnosis of the presence of Demodex mites but also to evaluate the therapeutic effects of medications to eliminate the mite infestation.Keywords: Demodex mites, Löffler’s alkaline methylene blue, blepharitis